JAMINAN PERLINDUNGAN HUKUM TERHADAP SIMPANAN NASABAH PADA BANK UMUM - Harniwati Harniwati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
One of the commercial bank facilities is to provide credit to the community. To fulfill these facilities the bank provides a form of ATM facility. Today's community needs for ATM facilities are getting higher. The community wants a transaction that is so fast, easy and safe and practical, that the community needs are responded by banking institutions by providing as many ATM facilities as possible that can be reached by the community using the ATM. The ease of withdrawal raises concerns about the safety of customer deposits, because ATMs are very vulnerable to causing losses to customers, this is because the ATM machine cannot detect whether the puller is the person who has the right or not. To anticipate this, a guarantee of legal protection is needed for customer deposits in commercial banks.